Komunikasi Partisipatif Masyarakat dalam Program Pemerintah Kota Bogor untuk Pengurangan Sampah Plastik - Ramadanti, Firli Diyanira; Nuraryo , Imam (KOMUNIKA, 2025)
This study explores the impact of participatory communication on the Bogor City Government's plastic waste reduction initiatives. Plastic waste poses a considerable challenge in Bogor, with daily generation reaching 779.81 tons in 2024, of which 15-20% is plastic. The research involved semi-structured interviews with five diverse individuals (students, workers, housewives, neighborhood leaders, and running club members) and an online survey of 56 respondents across different Bogor areas. Interview findings reveal that while residents are aware of waste's adverse effects and have personal efforts to reduce plastic, their engagement in government programs is hindered by unclear information regarding program specifics (such as location and timing) and inconsistent outreach. Questionnaire data supports these observations; most respondents learned about programs through neighborhood heads or official government social media, yet many could not participate due to inadequate information and invitations. Although a significant majority (82.1%) believe public participation is vital for program success, a large portion (62.5%) are unaware of how to submit feedback, and over half (51.8%) feel their input is not acted upon. The government's program implementation and public engagement are perceived as suboptimal, leading the community to desire regular meetings and stricter enforcement of regulations. In essence, a notable disconnect exists between government programs and public involvement due to ineffective participatory communication. Therefore, recommendations include strengthening clear information channels, leveraging neighborhood leaders' roles, developing accessible two-way communication mechanisms, improving implementation consistency and follow-up, launching creative educational campaigns, and fostering inter-stakeholder collaboration for sustainable waste management.